The representation of public opinion in reporting poll results on environment issues - Nagai, Kentaro (Frontiers in Communication, 2023)
This study examines how Japanese newspapers reporting opinion poll results represent a unified image of public opinion on environmental issues. It focuses on issue poll reporting to discuss how certain types of results are emphasized while others are excluded. First, news reports most highlight the anxieties and concerns of people vis-à-vis environmental issues, followed by individual willingness and practices undertaken to adopt environmentally friendly behavior such as energy conservation and recycling. Overall, the study identifies that headlines tend to prompt the impression that many respondents support this opinion. However, some media outlets that follow this trend are found to selectively highlight a single aspect of split opinion poll results in their headlines without noting the existence of a conflict. They use the second-person and collective nouns to interpret poll results denoting a distribution of opinions. The narrative subsequently implies a comprehensively united public opinion that indicates a certain direction. This article concludes that media representations of public opinions based on outcomes of public opinion polls on environmental issues in Japan legitimize existing political and economic structures, attributing the responsibility for environmental problems to individuals.